2005
DOI: 10.1007/s00404-005-0728-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of progesterone production in human term trophoblasts in vitro by CRH, ACTH and cortisol (prednisolone)

Abstract: The results suggest that CRH and ACTH directly modulate the endocrine function of trophoblasts in culture by downregulating progesterone production. Prednisolone on the other hand showed a stimulating effect on progesterone production in term trophoblast cells in vitro. Because blockade of progesterone is a possible mechanism involved in initiation of labor, we may speculate that CRH and ACTH are directly involved in the auto- or paracrine regulation of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…It has been suggested that this CRH-regulated metabolic barrier is part of a mechanism that prevents myometrial activation (28). By contrast, findings such as CRH stimulation of placental prostaglandin production and inhibition of progesterone production from placental trophoblast (29) might indicate that the actions of CRH help the myometrial transition from relaxation to active contractions.…”
Section: Placenta and Foetal Membranesmentioning
confidence: 99%
“…It has been suggested that this CRH-regulated metabolic barrier is part of a mechanism that prevents myometrial activation (28). By contrast, findings such as CRH stimulation of placental prostaglandin production and inhibition of progesterone production from placental trophoblast (29) might indicate that the actions of CRH help the myometrial transition from relaxation to active contractions.…”
Section: Placenta and Foetal Membranesmentioning
confidence: 99%
“…Two recent studies have demonstrated a reduction in the rate of preterm birth with intravaginal progesterone administration to women with premature cervical shortening3, 4. Progesterone is known to affect several cellular physiologies in each tissue of the reproductive tract including the cervix5–21.…”
Section: Introductionmentioning
confidence: 99%
“…The human placenta has been shown to express both subtypes of CRH receptors (Florio et al 2000). More recently, Jeschke and colleagues showed that the addition of CRH to the placental trophoblast cultures resulted in a decrease in progesterone release (Jeschke et al 2005). However, the effect of CRH produced locally in the placental trophoblasts on progesterone biosynthesis, and a detailed and quantitative analysis of the effects of CRH on all the enzymes needed for progesterone production as well as the specific CRH receptors responsible for the actions of CRH have not been performed.…”
Section: Introductionmentioning
confidence: 99%